Загальна та спеціальна дисциплінарна відповідальність - Жеребцов, Д. Є.; Zherebtsov, D. Ye. (Соціальне право. - 2019. - № 1. - С. 90-96, 2019)
Досліджено правове регулювання дисциплінарної відповідальності працівників. Обґрунтовано доцільність виокремлення загальної та спеціальної дисциплінарної відповідальності. Окресленоособливості спеціальної дисциплінарної відповідальності. Надано пропозиції з удосконалення національного законодавства, яке передбачає дисциплінарну відповідальність. Запропоновано у всіх спеціальних законах, які передбачають дисциплінарну відповідальність, чітко прив’язати всі дисциплінарні стягнення до конкретних дисциплінарних проступків.

The article is devoted to the study of legal regulation of disciplinary responsibility of employees. The expediency of separation of general and special disciplinary responsibility is substantiated. Specific features of special disciplinary responsibility are outlined. Proposals for improving national legislation providing for disciplinary liability are provided. In particular, it is proposed in all special laws that provide for disciplinary liability to clearly link all disciplinary penalties to specific disciplinary offenses.The peculiarities of disciplinary responsibility are presented, one of which is the use of penalties by the subject of employment relationship, namely the employer, which makes disciplinary responsibility one of the expressive powers of the employer in relation to the employee who has concluded an employment contract with him.The main differences between the special disciplinary responsibility and the general are noted, namely: 1) the circle of persons to whom it applies; 2) types of disciplinary sanctions; 3) the number of persons who may apply disciplinary sanctions; 4) the procedure for applying the penalties; 5) the procedure for appealing disciplinary penalties. It is substantiated that the special disciplinary responsibility of employees differs from the general broader content of disciplinary misconduct, more severe sanctions.An analysis of the national legislation was carried out, which allowed to identify a number of laws establishing the peculiarities of disciplinary responsibility. It is noted that all the above laws establish disciplinary liability only for a clearly defined circle of employees. Attention is drawn to the fact that although the aforementioned laws apply to public servants, they lack unanimity, above all in the amount of disciplinary sanctions that may be imposed on the employees concerned.It is proposed in all special laws that provide for disciplinary responsibility to clearly attach all disciplinary penalties to specific disciplinary offenses.

Исследовано правовое регулирование дисциплинарной ответственности работников. Обоснована целесообразность выделения общей и специальной дисциплинарной ответственности. Определены особенности специальной дисциплинарной ответственности. Даны предложения по усовершенствованию национального законодательства, предусматривающего дисциплинарную ответственность. Предложено во всех специальных законах, предусматривающих дисциплинарную ответственность, четко привязать все дисциплинарные взыскания к конкретным дисциплинарным проступкам.
Keywords: дисциплінарна відповідальність,; disciplinary liability; дисциплинарная ответственность; загальна дисциплінарна відповідальність; general disciplinary responsibility; общая дисциплинарная ответственность; спеціальна дисциплінарна відповідальність; special disciplinary responsibility; специальная дисциплинарная ответственность; правове регулювання; legal regulation; правовое регулирование; дисциплінарний проступок; disciplinary offense; дисциплинарный проступок; дисциплінарне стягнення; disciplinary action; дисциплинарное взыскание